1993
DOI: 10.1017/s0950268800050895
|View full text |Cite
|
Sign up to set email alerts
|

Phage typing of Vero cytotoxin-producingEscherichia coliO 157 isolated in the United Kingdom: 1989–91

Abstract: SUMMARYBetween 1989 and 1991 a total of 1092 Vero cytotoxin-producingEscherichia coliO 157 isolated in the United Kingdom were phage typed in the Laboratory of Enteric Pathogens (LEP). Twenty-three phage types was identified, the most frequent being types 2 (36·1%), 49 (29·6%), 1 (10·3%) and 4 (8·9%). Although isolations of O 157 VTEC have increased each year from 1 in 1982 to 532 in 1991, the predominant phage types have remained unchanged although the proportion of strains belonging to types 2 and 49 has inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The predominant phage types identified among the 0157 VTEC isolates characterized in this study correspond with the observation by Frost and coworkers [19]. Among a total of 1092 0157 VTEC strains isolated in the UK between 1989 and 1991, they identified types 2 (36-1%), 49 (29-6%), 1 (10-3%) and 4 (8-9%) the most frequently.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The predominant phage types identified among the 0157 VTEC isolates characterized in this study correspond with the observation by Frost and coworkers [19]. Among a total of 1092 0157 VTEC strains isolated in the UK between 1989 and 1991, they identified types 2 (36-1%), 49 (29-6%), 1 (10-3%) and 4 (8-9%) the most frequently.…”
Section: Discussionsupporting
confidence: 89%
“…Among a total of 1092 0157 VTEC strains isolated in the UK between 1989 and 1991, they identified types 2 (36-1%), 49 (29-6%), 1 (10-3%) and 4 (8-9%) the most frequently. Frost and colleagues [19] also observed that strains of phage types 2 and 49 carried only VT2 genes. It is remarkable that, unlike phage types 2 and 4, 0157 VTEC phage type 49 has not been reported from North America [20].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Flagella antigen H7 was the most common H type (88%) of 0 157 VTEC, the remaining 12 % being non-motile. The most frequently encountered phage types of E. coli 0 157 were 2, 49, 1 and 4 [19]. The most common VT gene type was VT2 only (79%) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid analysis of 0157 VTEC can be used to identify strains in outbreaks and sporadic cases of infection (Scotland et ul. 1987;Frost et al 1993). Virtually all 0157 VTEC isolates carry a plasmid with a molecular weight of about 60 x 10" but certain strains carry additional plasmids.…”
Section: Genotypic Testsmentioning
confidence: 99%